1990
DOI: 10.1530/jrf.0.0880241
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of embryo-derived platelet-activating factor act by inhibiting the ability of the mouse embryo to implant

Abstract: This study utilized the transfer of preimplantation embryos to pseudo-pregnant mice to determine whether PAF-antagonists act primarily on the maternal or embryonic components of implantation. The first experiment used reciprocal embryo transfers, in which blastocysts from mice treated with PAF antagonist (SRI 63-441) or saline (controls), from Days 1 to 4 of pregnancy, were transferred to Day-3 pseudo-pregnant recipients which were also treated with SRI 63-441 or saline on Days 1-4 of pregnancy. The antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Thus, the receptors' response to IP 3 is sensitized by calcium. Indeed it is suggested that the IP 3 R acts as a computation switch capable of integration of inputs from several sources that lead to summative conformational changes that modulate its response to IP 3 [16,17]. Thus, highly localized increases in [Ca 2ϩ ] i due to calcium influx in response to PAF may allow store release to occur in response to relatively low concentrations of IP 3 generated by PAF action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the receptors' response to IP 3 is sensitized by calcium. Indeed it is suggested that the IP 3 R acts as a computation switch capable of integration of inputs from several sources that lead to summative conformational changes that modulate its response to IP 3 [16,17]. Thus, highly localized increases in [Ca 2ϩ ] i due to calcium influx in response to PAF may allow store release to occur in response to relatively low concentrations of IP 3 generated by PAF action.…”
Section: Discussionmentioning
confidence: 99%
“…PAF is produced de novo from simple substrates by the zygote [9,10], and its release requires extracellular albumin [11,12]. On release, it acts back on the preimplantation embryo in an apparently receptor-dependent manner to enhance embryo metabolism and the rate of cell-cycle progression [13][14][15], and it results in enhanced embryo survival and development [2,5,[16][17][18]. Embryo-derived PAF must act by the embryonic 2-cell stage for normal embryo survival to ensue [19].…”
Section: Introductionmentioning
confidence: 99%
“…1-O-alkyl-2-acetyl-sn-glyceryl-3-phosphocholine (platelet-activating factor, PAF) was the first characterized factor released by the preimplantation embryo to be identified (O'Neill, 1985a;O'Neill, 1985b). It was subsequently shown that PAF also stimulated embryo metabolism , cell cycle progression (Roberts et al, 1993) and embryo viability Spinks and O'Neill, 1988;Spinks et al, 1990), thereby providing evidence for an autocrine loop in the early embryo.…”
Section: Introductionmentioning
confidence: 99%
“…SRI 63-441 treatment of donor blastocysts reduced their implantation rate in uteri of pseudopregnant recipient mice. At the same time, systemic treatment of the recipient female had practically no signifi cant effect [113]. Culture in the presence of PAF increased the mitotic index of blasto cysts while the PAF-receptor antagonist WEB 2086 blocked the rise [114],…”
Section: Platelet-activating Factormentioning
confidence: 96%
“…Progesterone requirement is absolute. 112 Biol Signals 1996;5: [111][112][113][114][115][116][117][118][119][120][121] Estrogen may also be required, but only tran siently. The coarser (more traumatic) the in duction stimulus, the less stringent the estro gen requirement.…”
Section: Introductionmentioning
confidence: 99%